Reduction of Saccharomyces cerevisiae Pom34 protein level by SESA network is related to membrane lipid composition - Sezen, Bengu (Oxford Univ Press, 2015)
Various pathways block initiation of translation of the bulk of mRNAs in response to membrane stress, amino acid starvation and unfolded proteins. In contrast, SESA, a network of proteins comprising Smy2, Eap1, Scp160 and Asc1, is a novel inhibitor of translation initiation of specific mRNAs. SESA binds POM34 mRNA in response to failure in spindle pole body (SPB) duplication process and inhibits its initiation of translation. We herein report that Pom34 protein level is reduced also in cells with altered membrane lipid composition upon treatment with various chemicals and show that SESA-induced downregulation of Pom34 is crucial for viability of cells with a disturbed nuclear envelope. Thus, we propose that SESA's action in SPB duplication process is dependent on the alteration of membrane lipid composition to facilitate the insertion process.
Keywords: spindle pole body; Pom34; membrane lipid composition; translational regulation; Mps2; Smy2